Pengetahuan Perawat Tentang Keselamatan Pasien Dengan Perilaku Kepatuhan Melaksanakan Pencegahan Pasien Resiko Jatuh - Rini Fahriani Zees; Hendrik Prayitno Luawo; Ahmad Pakaya (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2021)
Compliance is a series of behavior according to rules and discipline (Pranoto, 2007). One of the internal factors that affect compliance is knowledge. Nurse knowledge about patient safety is something that nurses must know because it is a variable to measure and evaluate the quality of nursing services that have an impact on health services. One of the indicators for implementing patient safety is maintaining the safety of patients who are at risk of falling.This study aims to determine whether there is a relationship between the knowledge of nurses about patient safety and compliance behavior in implementing the prevention of fall risk patients at Toto Kabila Hospital. Correlational descriptive with a cross-sectional design using the chi-square test on 59 nurses on duty in the IGD, Internal, Surgery, and ICU rooms with Cluster Sampling. The results showed that there was a relationship between nurses' knowledge about patient safety and nurses' compliance in carrying out the risk of falling patients. (ρ= 0.001 with ; 0.05). The improvement of nursing competence for nurses can be carried out by hospital management to increase nurses' knowledge regarding the prevention of falls at risk of patients through workshops and training activities.